Experimental Design Applied to the Optimization and Partial Characterization of Pectin Liase from a Newly Isolated Penicillium brasilianum - Zeni,Jamile (2014)
Penicillium brasilianum was previously isolated from tea and identified by molecular biology technique. A Plackett-Burman design, followed by a complete second order design was used for the screening of most important factors and to maximize the pectin liase (PMGL) activity, respectively. The maximum PMGL activity by P. brasilianum achieved was 9.0 U/mL after 48 h of cultivation in a medium containing pectin (33.0 g/L), yeast extract (30.0 g/L) and potassium phosphate (2.0 g/L) at 30ºC, with a stirring rate of 180 rpm, initial pH 5.5 and 5x106spores/mL inoculum size. The kinetic evaluation in terms of substrate consumption demonstrated that the maximum production of PMGL was at 72 h, and 40% of the total organic carbon, 25% of the nitrogen, 88% of the magnesium, 13% of the potassium and 66% of the iron were consumed. The pH remained almost stable during the whole period of production (5.33 to 4.9). The partial characterization of the crude PMGL enzyme extract showed optimal pH and temperature of 5.5 and 37°C, respectively.